¡Dejémoslos leer! - Báez Cruz, Eduardo (2004)
The author used this phrase to begin his opening lecture at the 6 th Seminar Work shop “Libros, alas de la Creatividad: La lectura, ventana a la diversidad” (“Books, the wings of Creativity: Reading, a window to diversity”), organized by División de Educación Básica del Centro de Investigación y Docencia en Educación (CIDE) of University Nacional, Costa Rica (CIDE's Department of Basic Education) in June of 2004. It narrates the experience of “Libros para Niños” (“Books for Children”), a non-governmental organization that has been encouraging and promoting the reading habit in Nicaragua for eleven years. Several projects developed by that NGO are presented, such as “Dame de leer” (Give me something to read), for preschoolers; the “Bibliotecaulas” (“Libraries within classrooms”), applied to elementary school and “Rincones de Cuentos” (“Story Corners”) or children's reading rooms, developed along with the community. A sample activity carried out whit sixth graders is presented and analyzed; moreover, important conclusions about the way in which teachers promote the reading habit on a regular basic are drawn.